Outcome of phacoemulsification without anti-vascular endothelial growth factor in patients with treatment naïve diabetic retinopathy - Rijal, Roshija Khanal; Adiga, Sushant; Pokharel, Kaushal; Dhakal, Sabin; Rijal, Thaneshwar; Khadka, Sitaram (Nepalese Journal of Ophthalmology, 2022)
Introduction: This retrospective, non-randomized, observational study was conducted at ASG Eye Hospital, Kathmandu to evaluate the outcome of phacoemulsification without anti-Vascular Endothelial Growth Factor (VEGF) in patients with treatment naïve diabetic retinopathy. Materials and methods: Records of all patients who underwent phacoemulsification without Bevacizumab in treatment of naïve patients with any grade of non-proliferative Diabetic Retinopathy (NPDR) were seen. Pre-operative and post-operative visual acuity along with central macular thickness (CMT) was compared. Results: The study comprised 32 eyes of 20 patients with treatment naïve non-proliferative Diabetic Retinopathy who underwent phacoemulsification. Twelve were men and eight were women with an average age of 69.2 years (range 55 years to 83 years). The average preoperative central macular thickness as measured on optical coherence tomography was 254.63± 20.25 microns and 1-month postoperative central macular thickness was 254.72± 19.96 microns; the study did not find any significant difference (p-value 0.918). The average difference in the central macular thickness between the 1-month postoperative and preoperative values was 0.09 microns. Conclusion: Uneventful phacoemulsification in eyes with treatment naïve diabetic retinopathy does not cause an increase in central macular thickness after surgery and thus anti-Vascular Endothelial Growth Factor as an adjunct is not mandatory.